Pengertian Wirausaha dan Karakteristik Wirausaha - Fahri Sahrul Ramadhan; Abdul Hafid; Ardiansyah Ardiansyah; Ujang Nurjaman (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Entrepreneurs play a significant role in the economic development of a country. This is because entrepreneurs bring about many changes in the development of a nation. One of the challenges faced by the Indonesian nation is how to foster and enhance entrepreneurship. Considering the number of entrepreneurs still below the minimum standard of two percent, the economic growth of Indonesia can be said to be suboptimal. Furthermore, a more fundamental understanding of entrepreneurship must be continually pursued by various parties, including within the scope of formal education, professional education, and also by the state as a primary component. This study aims to obtain comprehensive information about the definition of entrepreneurship and the characteristics of entrepreneurs using the literature study research method (library research). This research uses qualitative data, which cannot be measured on a numeric scale. The data sources used are secondary data related to the research object, which comes from books, scientific journals, seminar papers, and others.